PERSEPSI WISATAWAN TERHADAP OBJEK WISATA DURIAN DI DESA BIIH KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Erly Wahyuni; Abdi Fithria; Siti Saidah (Universitas Lambung Mangkurat, 2020)
Durian tourism objects in the village of Biih have natural potential as a tourism attraction. This tour is interesting because it only exists in the durian season. The purpose of this study was to determine the perception of tourists visiting durian tourism objectsand get information as a reference for the development of durian tourism objects. The method used is direct observation to the field by conducting interviews with tourists in accordance with the contents of the questionnaire. Based on information from tourists who are respondents namely cleanliness and public facilities that exist in durian tourism is not good, while for road access, tourist attraction, and security there is enough. Based on the rating category of the perception rating of tourists towards the development of durian tourism objects in the village it is classified into the medium category. Durian tourism in the village is a newly developed tourist spot and still requires special attention to be further developed. There are still many things that must be developed from durian tourism both from road access to the location ad facilities provided and also the cleanliness of tourist attractions.Keywords: Perception; Traveler; Durian tourism objects.